Natural Radioactivity Hazard Assessment on Soil in Kassala Town-Sudan - Hamouda Belal, Suleiman Awad (Gezira Journal of Engineering and Applied Sciences, 2020)
Abstract      Human beings have always been exposed to natural radiation, which is mainly due to the activity concentration of primordial radio nuclides. In this study, measure the concentration of natural activity radiation, absorbed dose rate, annual effective dose (indoor/outdoor) and assessment of radiation hazard index are measured for some soil sample from various geographical locations in Kassala Town - Kassala State – Sudan , for the elements 226 Ra, 232 Th and 40 K, using gamma-ray spectrometry. The study conduct to the average concentration for 226 Ra, 232 Th and 40 Kwere found to be 18.19 Bq/Kg, 19.56 Bq/Kg and732.37 Bq/Kg respectively. The calculated average absorbed dose rate was 50.75nGy/h, annual effective dose were0.25mSv/y(indoor), 0.06mSv/y(outdoor) and the radiation hazard index was 0.29. The study conclude that the average concentration of all elements in the study is less than the average worldwide 226 Ra =35 Bq/Kg),( 232 Th=30 Bq/Kg ) except 40 K( 40 K=400 Bq/Kg) and also the absorbed dose rate and annual effective dose (indoor/outdoor) are less than the average worldwide(60 nGy/h), (0.41mSv/y(indoor), (0.07mSv/y(outdoor). The assessment of radiation hazard index to the soil of Kassala Town is more less than the standard ( .